(Un)Constitutional Amendments and Cameroon Constitutions: Strange Bedfellows with the Rule of Law and Constitutionalism. Issue 1 (February 2021) - Wanki, Justin Ngambu
Abstract : The article examines unconstitutional constitutional amendments in the constitutional order of Cameroon dating back from 1960 to 2008. The examination reveals that all the amendments engaged within this period fail to comply with the rule of law and constitutionalism, facilitated and abetted by the three branches of government in Cameroon. The article ends by emphasising that since power is held by government only as a trust for the benefit of the people, it entails that constitutional amendments should be undertaken only when they are in the interests of the people who are the ultimate beneficiaries of the trust.